A combination of YM-155, a small molecule survivin inhibitor, and IL-2 potently suppresses renal cell carcinoma in murine model - Guo, Kai (Oncotarget, 2015)
YM155, a small molecule inhibitor of the antiapoptotic protein survivin, has been developed as a potential anti-cancer drug. We investigated a combination therapy of YM155 and interleukin-2 (IL-2) in a mouse model of renal cell carcinoma (RCC). YM155 caused cell cycle arrest and apoptosis in renal cancer (RENCA) cells. Next, luciferase-expressing RENCA cells were implanted in the left kidney and the lung of BALB/c mice to develop RCC metastatic model. In this orthotopic renal and metastatic lung tumors models, YM155 and IL-2 additively decreased tumor weight, lung metastasis, and luciferin-stained tumor images. Also, the combination significantly suppressed regulatory T cells and myeloid-derived suppressor cells compared with single agent treatment. We suggest that a combination of YM155 and IL-2 can be tested as a potential therapeutic modality in patients with RCC.